Aplikasi Monitoring Pasien Tuberkulosis di Puskesmas Kebayoran Lama - kiki kusumawati (Jurnal Manajemen Informatika JAMIKA, 2023)
Health is an important part that must be owned by every human being as a creature of God who is literally part of a social creature and society and needs a decent life to support himself and the surrounding environment. The variety of diseases in Indonesia that hurt its people also has many variations, from non-lethal to deadly diseases such as Tuberculosis disease or commonly known as TB disease. The current system at the Kebayoran Lama South Jakarta Health Center in terms of monitoring the treatment of TB patients is still carried out conventionally, 1) where officers collect patient data written on a treatment card which sometimes if the treatment card can be lost and possibly damaged, so it must be made again, causing a buildup of patient treatment cards, 2) sometimes the treatment card that is usually carried is lost or damaged, 3) the patient forgets when to come back for control and the schedule for taking the medicine, so that it can cause the patient to have to repeat the treatment from the beginning if the time to take the medicine is not according to schedule. Based on these problems, it is necessary to create an application that can strive to monitor patient health in mobile drug administration. The development of this system uses a prototype method model with the aim of this application being able to provide information related to monitoring patient health through regular consumption of drugs according to schedule.